Analisis kecelaruan membaca bahasa Melayu pelajar kelas intervensi awal membaca dan menulis (KIA2M) / A. Jailani bin Che Abas - A. Jailani, Che Abas (2012)
The objective of this research is to study on the confusion in reading Malay language among year one pupils involve with program known as ‘Kelas Intervensi Awal Membaca dan Menulis (KIA2M).This research hopes to help teachers to plan for the group as the issue of illiteracy has been seriously attended to . The seriousness of this issue can be seen when the program is replaced with Literacy and Numeracy programs (LINUS), that is National Key Result Areas (NKRA) as a main focus by the Ministry Of Education Malaysia. A total of 22 pupils involved in this research representing 220 Year One pupils from primary school. Studies conducted based on the question of the Diagnostic Tests provided by the ministry. The questionnaires are in accordance with construct deems appropriate to the level and age of pupils. A modified teaching method used as a model which is closely related to student formative experience. Statistical Package for Social Science (SPSS) was used to analyze data in a descriptive and cross tabulation. The method used is a clear tabulation of data in meeting the objectives of the research. Results showed Malay Language disorder occurs most often in the eleventh construct while reading and to understand simple sentences. The next objective shows early education for pupils also play an important role as research shows that pupils from private kindergartens did less of reading disorders while reading the Malay language than the ‘KEMAS’ kindergarten and preschool at government school. The third objective revealed that the male students showed less disorder than girls do when reading and writing the Malay language. This research will help teachers identify the disorder in reading among year one pupils, thus teachers will take further action in order to achieve the objectives of teaching and learning.